Proceedings of the 2nd International Conference on Education: Current Issues and Digital Technologies (ICECIDT 2022) 2022
DOI: 10.2991/978-2-494069-02-2_20
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Implicit Stratified Teaching to English Reading Teaching in Junior Middle School

Abstract: Under the current teaching system in China, teachers are still adopting the same teaching contents, teaching objectives, teaching activities and the same evaluation methods to all the students in one class. This will probably make highlevel students feel that the classroom is not challenging, and lower-level students can't keep up with others and lose confidence gradually. In this case, stratified teaching emerged to help the teacher to pay attention to the individual differences of students and to meet the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Wang Fuzhi, a thinker in the Qing Dynasty, advocated that "The students are not uniform, so we have to go in for each person," pointing out that there are individual differences between students, and personalized teaching should be carried out according to the differences between them. These ideas have thoroughly bred the ideas and concepts of stratified teaching (He, 2014).…”
Section: Research Background Of Stratified Teachingmentioning
confidence: 99%
“…Wang Fuzhi, a thinker in the Qing Dynasty, advocated that "The students are not uniform, so we have to go in for each person," pointing out that there are individual differences between students, and personalized teaching should be carried out according to the differences between them. These ideas have thoroughly bred the ideas and concepts of stratified teaching (He, 2014).…”
Section: Research Background Of Stratified Teachingmentioning
confidence: 99%
“…However, many teachers still use the traditional way to take their English reading teaching, from the explanation of words to the translation of the full text, the explanation and practice of grammatical structure and so on. [1] indicated that in most rural areas of our country, many schools still adopt traditional teaching methods in English classroom. This way emphasizes the language form too much and neglects the cultivation of reading strategies and skills, which will lead to the low enthusiasm in reading class.…”
Section: Introductionmentioning
confidence: 99%